Text To Speech Bahasa Indonesia Pada Pesan SMS Dengan Konverter PDU - Siregar, Dodi (STMIK TIME, 2014)
This research aims to design and know how to take a short message (SMS) that is in the mobile phone into the computer, the process of making a short message (SMS) should be done by converting the PDU so short messages (SMS) can be understood, a short message information that have been read by the computer will be translated into sound or commonly called the text to speech, text to speech produced is Indonesian language.